Pengaruh Manajemen Spiritual Leadership Dalam Pemerataan Ekonomi Sektor Riil - Sumadi Sumadi; Yudi Siyamto (Jurnal Ilmiah Ekonomi Islam, 2019)
This study aims to analyze the characteristics of culinary service business leaders in Surakarta, also to analyze the spiritual role of leadership in the growth of the creative economy in Surakarta. This research method is a quantitative method with an explanation approach. There are 5 (five) key informants (informants) who will be interviewed in this study consisting of leaders in the culinary service sector business in Surakarta. The results of data analysis research obtained that the results obtained that the variable vision, hope/ faith, altruistic love, meaning / calling, membership, commitment and job satisfaction have a significant positive influence on spiritual lesdership.